Lysosomal TRPML1 triggers global Ca2+ signals and nitric oxide release in human cerebrovascular endothelial cells - Brunetti, Valentina; Berra-Romani, Roberto; Conca, Filippo; Soda, Teresa; Biella, Gerardo Rosario; Gerbino, Andrea; Moccia, Francesco; Scarpellino, Giorgia (Frontiers in Physiology, 2024)
Lysosomal Ca2+ signaling is emerging as a crucial regulator of endothelial Ca2+ dynamics. Ca2+ release from the acidic vesicles in response to extracellular stimulation is usually promoted via Two Pore Channels (TPCs) and is amplified by endoplasmic reticulum (ER)-embedded inositol-1,3,4-trisphosphate (InsP3) receptors and ryanodine receptors. Emerging evidence suggests that sub-cellular Ca2+ signals in vascular endothelial cells can also be generated by the Transient Receptor Potential Mucolipin 1 channel (TRPML1) channel, which controls vesicle trafficking, autophagy and gene expression. Herein, we adopted a multidisciplinary approach, including live cell imaging, pharmacological manipulation, and gene targeting, revealing that TRPML1 protein is expressed and triggers global Ca2+ signals in the human brain microvascular endothelial cell line, hCMEC/D3. The direct stimulation of TRPML1 with both the synthetic agonist, ML-SA1, and the endogenous ligand phosphatidylinositol 3,5-bisphosphate (PI(3,5)P2) induced a significant increase in [Ca2+]i, that was reduced by pharmacological blockade and genetic silencing of TRPML1. In addition, TRPML1-mediated lysosomal Ca2+ release was sustained both by lysosomal Ca2+ release and ER Ca2+- release through inositol-1,4,5-trisphophate receptors and store-operated Ca2+ entry. Notably, interfering with TRPML1-mediated lysosomal Ca2+ mobilization led to a decrease in the free ER Ca2+ concentration. Imaging of DAF-FM fluorescence revealed that TRPML1 stimulation could also induce a significant Ca2+-dependent increase in nitric oxide concentration. Finally, the pharmacological and genetic blockade of TRPML1 impaired ATP-induced intracellular Ca2+ release and NO production. These findings, therefore, shed novel light on the mechanisms whereby the lysosomal Ca2+ store can shape endothelial Ca2+ signaling and Ca2+-dependent functions in vascular endothelial cells.